The Moderating Effect of Competition on The Leverage-Performance Relation: Evidence from Vietnam - Nguyen Le Hoa Tuyet,; Le Tan Nghiem,; Le Khuong Ninh, (Asian Academy of Management Journal, 2024)
This paper examines the moderating effect of competition on the relationship between financial leverage and firm performance in Vietnam. Using a dataset created out of 352 firms listed on Vietnam’s stock exchanges in 2015–2019, this paper estimates both the leverage-performance relation and the dependence of this nexus on market competition. The two-step system generalised method of moments is used to tackle the endogeneity, unobserved heterogeneity, and autocorrelation problems in our model estimation. The findings reveal a negative leverage-performance nexus, and increased competition hurts this relationship. In highly competitive markets, debts become more expensive, thus leading to increased financial pressures on leveraged firms. The fiercer competition also creates a risky business environment, so leveraged firms may fail when operating inefficiently and failing to satisfy their debt obligations. Given the results, this paper proposes recommendations on using financial leverage to improve firm performance.